Calcium Extrusion Pump PMCA4: A New Player in Renal Calcium Handling? - Ellen P M van Loon; Robert Little; Sukhpal Prehar; René J M Bindels; Elizabeth J Cartwright; Joost G J Hoenderop (PLoS ONE)
Calcium (Ca2+) is vital for multiple processes in the body, and maintenance of the electrolyte concentration is required for everyday physiological function. In the kidney, and more specifically, in the late distal convoluted tubule and connecting tubule, the fine-tuning of Ca2+ reabsorption from the pro-urine takes place. Here, Ca2+ enters the epithelial cell via the transient receptor potential vanilloid receptor type 5 (TRPV5) channel, diffuses to the basolateral side bound to calbindin-D28k and is extruded to the blood compartment via the Na+/Ca2+ exchanger 1 (NCX1) and the plasma membrane Ca2+ ATPase (PMCA). Traditionally, PMCA1 was considered to be the primary Ca2+ pump in this process. However, in recent studies TRPV5-expressing tubules were shown to highly express PMCA4. Therefore, PMCA4 may have a predominant role in renal Ca2+ handling. This study aimed to elucidate the role of PMCA4 in Ca2+ homeostasis by characterizing the Ca2+ balance, and renal and duodenal Ca2+-related gene expression in PMCA4 knockout mice. The daily water intake of PMCA4 knockout mice was significantly lower compared to wild type littermates. There was no significant difference in serum Ca2+ level or urinary Ca2+ excretion between groups. In addition, renal and duodenal mRNA expression levels of Ca2+-related genes, including TRPV5, TRPV6, calbindin-D28k, calbindin-D9k, NCX1 and PMCA1 were similar in wild type and knockout mice. Serum FGF23 levels were significantly increased in PMCA4 knockout mice. In conclusion, PMCA4 has no discernible role in normal renal Ca2+ handling as no urinary Ca2+ wasting was observed. Further investigation of the exact role of PMCA4 in the distal convoluted tubule and connecting tubule is required.